DIGITAL ACCESS, ONLINE TRAINING, AND TEACHING MOTIVATION: THE MEDIATING ROLE OF TECHNOLOGY SELF-EFFICACY - Siti Nahriah Aprianti; Mursyidah, Himmatul; Warni, Warni (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study investigates the effects of digital access and online training on teaching motivation, with technology self-efficacy as a mediating variable. Grounded in Social Cognitive Theory, the study integrates structural and psychological factors to explain teacher motivation in digital learning contexts. A quantitative explanatory survey was conducted involving 300 senior high school teachers in Tangerang Regency, Indonesia, selected using proportional random sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 5,000 bootstrap resamples. The findings indicate that digital access (β = 0.491, p < 0.001) and online training (β = 0.523, p < 0.001) significantly influence technology self-efficacy. Technology self-efficacy, in turn, significantly affects teaching motivation (β = 0.251, p < 0.001). However, the direct effects of digital access (β = 0.131, p = 0.057) and online training (β = 0.106, p = 0.081) on teaching motivation are not significant. Mediation analysis reveals that technology self-efficacy fully mediates these relationships. This study contributes to the literature by demonstrating that structural factors alone are insufficient to enhance teacher motivation unless internalized through efficacy beliefs. The findings provide practical implications for designing teacher development programs that prioritize mastery-based training and confidence-building strategies.